2013
DOI: 10.1055/s-0033-1356476
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Markers of Ovarian Reserve

Abstract: Ovarian reserve and its utilization, over a reproductive life span, are determined by genetic, epigenetic, and environmental factors. The establishment of the primordial follicle pool and the rate of primordial follicle activation have been under intense study to determine genetic factors that affect reproductive lifespan. Much has been learned from transgenic animal models about the developmental origins of the primordial follicle pool and mechanisms that lead to primordial follicle activation, folliculogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 186 publications
1
37
0
Order By: Relevance
“…--substantially overlapping the list assembled by Wood and Rajkovic [86], who also summarize substantial effects of many of the candidate genes in mice. Instead, the GWAS hits were startlingly different from the candidate gene list.…”
Section: Gwas Variants Compared To Poi Reports and "Candidate Genes"mentioning
confidence: 86%
See 1 more Smart Citation
“…--substantially overlapping the list assembled by Wood and Rajkovic [86], who also summarize substantial effects of many of the candidate genes in mice. Instead, the GWAS hits were startlingly different from the candidate gene list.…”
Section: Gwas Variants Compared To Poi Reports and "Candidate Genes"mentioning
confidence: 86%
“…As in other GWAS studies, the DNA variants revealed explained only part (up to 4.1%) of the variance of age of menopause in the populations studied. Nevertheless, their importance is increased by confirmatory GWAS findings in other ethnic groups (reviewed by [86]). Furthermore, other sources of variation, like the FRAXA expansion and FRAXE microdeletions, were not assessed and analyses taking into account insertion/deletions and rare alleles and looking at larger cohorts will certainly explicate more of the genetic contribution to the timing of reproductive lifespan.…”
Section: Genetic Variants Associated With Regulation Of Timing In Normentioning
confidence: 99%
“…The nuclear receptor 5A1 (NR5A1) and transforming growth factor β receptor (TGFBR1) genes, which are located on chromosome 9q34 and 9q22 near the ABO locus, are related to ovarian function. Therefore, recombination may occur between these genes and the ABO type genes at a relatively high rate, which would increase the likelihood of these genes being inherited together with ABO [19, 20]. Additionally, variation in genes as phased haplotypes might affect the folding and levels of other proteins and thus increase the chances of inheriting specific allele combinations together [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Women with POF present with amenorrhea (primary or secondary) and hypoestrogenic symptoms (i.e., hot flashes, vaginal dryness, premature osteoporosis). POF is genetically heterogeneous (2), with few genes identified, and can be idiopathic and nonsyndromic or part of a genetic syndrome.…”
Section: Introductionmentioning
confidence: 99%